The Scientific Research On Natural Capital: A Bibliometric Network Analysis - Buonocore, Elvira; Picone, Flavio; Russo, Giovanni Fulvio; Franzese, Pier Paolo (Journal of Environmental Accounting and Management, 2026)
Natural capital can be defined as the stock of natural resources generating a “natural income” in terms of valuable flows of different types of ecosystem goods and services. According to “strong sustainability”, natural capital is irreplaceable with manufactured capital and it ensures a life support system vital for human well-being. In this study, the global scientific literature on natural capital was explored by performing a bibliometric network analysis. The investigation of the networks of authors, countries, journals, and keywords allowed a comprehensive overview of the scientific literature on natural capital. Results showed an increase in the attention given to the topic of natural capital worldwide. The combined use of social network analysis and bibliometrics proved to be a promising approach for exploring the scientific literature by applying systems thinking in bibliometric science.